Analysis of Quality Status and Prediction of the Distribution of Temperature, DO, pH, Salinity, and Brightness of Sea Water in the Saugi Island Area Based on Spatial Inverse Distance Weighting - Nasrul, Nasrul; Qaiyimah, Dinil; Nurfadilah, Nurfadilah; Haris, Haris; Amdah, Misdar; Mulianti, Mulianti; Hidayah, Nurul (International Journal of Applied Biology, 2025)
Marine waters are crucial for maintaining marine ecosystems and achieving sustainable environmental sustainability. This research aims to analyze the quality status and predict the distribution of temperature, brightness, salinity, pH, and dissolved oxygen (DO) concentrations as indicators for assessing marine water quality. The study employs descriptive statistics to process laboratory test results and field measurements of the tested parameters. Marine water quality status is determined by calculating the percentage of limiting parameters and establishing maximum and minimum values for each parameter as benchmarks. The prediction of concentration distribution for temperature, brightness, salinity, pH, and DO is carried out using Spatial Inverse Distance Weighting (IDW) analysis, which illustrates the concentration distribution of each parameter based on data input in ArcGIS Pro software. The findings reveal varying quality statuses at different sampling points, with good conditions at points 4 and 5, where limiting parameter percentages are 22%. Medium quality status is observed at points 2 and 7 (33%) and points 3 and 6 (44%). Poor conditions are noted at points 1 and 8, with a 55% limiting parameter percentage. The study recommends this research as a valuable reference for the community and government to support marine ecosystem preservation and Sustainable marine ecosystem.